Vulnerability Analysis of Small Fishermen's Household Livelihoods in Tegal City (Universitas Negeri Semarang, 2019)
Small fishermen are known for being very dependent on fluctuating fish resources and the nature of open access fisheries which together cause resource degradation, poverty and marginalization. The problems of small-scale fisheries include low economic performance and limited ability or expertise in facing global pressure, including climate change. Based on the problems faced by small fishermen as described, it is certainly a separate danger on the fishermen's livelihood system which causes the livelihoods of small fishermen to be more vulnerable. The purpose of this study was to analyze the level of vulnerability of the livelihoods of small fishermen’s households. This research used quantitative methods supported by qualitative data. The study was conducted in Muarareja Sub-Districts, Tegal City, Central Java. This study was conducted using a livelihood vulnerability index questionnaire and in-depth interviews. Data was collected from forty respondents. This study found the fact that small scale fishermen both top and bottom layer in Muarareja village in which this study was conducted was not too vulnerable (resilient). However, they have a fairly good adaptive capacity with the use of capacity by using the livelihood capital optimally upper layer fishermen tend to use physical and financial capital to carry out exploitation and spatial strategies. On the other hand, the lower layers of fishermen mostly use their social capital such as affiliation with groups, high trust and patron-client systems based on moral economy.